Plant-closing decisions and the market value of the firm - Blackwell, David W; Marr, M.Wayne; Spivey, Michael F (Journal of Financial Economics, 1990)
We investigate the underlying causes and the announcement effects of plant closings. The closing in our sample do not appear related to takeover activity. Instead, they appear motivated by declining firm profitability. Firms announcing closings have lower earnings than market or industry medians; earnings typically improve slightly after the announcement. We find a negative stock-market reaction to plant-closing announcements.